Alternative storm-water management scenarios for developing countries in urban contexts. Issue 4 (20th May 2021) - Gogate, Nivedita G; Jedhe, Yamini
Abstract : The rapid expansion of cities has tremendously increased the storm water volume, which frequently causes local flooding. Conventional drainage systems are often unable to sustain these run-off volumes. This has caused an appreciable rise in the implementation of water-sensitive urban design techniques to manage the storm water. Incorporation of sustainable strategies becomes even more critical for developing countries, where there is continued demand for expanding urban water infrastructure. This study presents innovative alternate scenarios for managing storm water sustainably for urban areas in developing countries. The scenarios consist of combinations of multiple alternate measures provided in a decentralised manner. The study also seeks to evaluate the hydrologic performance of these scenarios. A simple methodology, based on the Natural Resources Conservation Service curve number method and Arc-CN Runoff tool, is developed for analysing hydrologic benefits and is applied to a sub-catchment in Pune City, India, to demonstrate its utility for urban areas. The results clearly indicate the effectiveness of implementing these scenarios in improving urban hydrological response. The current study is intended to appraise urban local bodies and stakeholders regarding sustainable, decentralised ways of managing storm water and their potential hydrological impacts at the watershed scale.